2014
DOI: 10.1128/jcm.02973-13
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing of an Emerging Cryptosporidium hominis Subtype in the United States

Abstract: The United States has experienced a substantial increase in the reported incidence of cryptosporidiosis since 2005. Accompanying this is the emergence of a new subtype of Cryptosporidium hominis based on variation at the 60-kDa glycoprotein (gp60) locus, IaA28R4, which has become a frequently identified subtype in both sporadic and outbreak-related cases. In this study, using multilocus sequence typing (MLST) at eight genetic loci, we characterized 62 specimens of IaA28R4 and 33 specimens of three other gp60 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 22 publications
2
34
0
1
Order By: Relevance
“…This is also a common C . hominis subtype identified in humans worldwide [28, 79, 80, 81, 74]. The source and human health significance of the novel C .…”
Section: Discussionmentioning
confidence: 99%
“…This is also a common C . hominis subtype identified in humans worldwide [28, 79, 80, 81, 74]. The source and human health significance of the novel C .…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies have shown a panmictic population structure with frequent recombination in C. parvum (Herges et al 2012;De Waele et al 2013), whereas others have demonstrated the existence of a flexible reproductive strategy (co-occurrence of panmictic, clonal or epidemic structure) in this species (Tanriverdi et al 2008;Drumo et al 2012). Similarly, some genetic studies conducted on C. hominis identified largely a clonal population structure (Mallon et al 2003;Gatei et al 2007;Li et al 2013;Feng et al 2014), whereas others showed the common occurrence of genetic recombination in C. hominis in developing countries (Widmer and Sullivan, 2012). In areas with an overall clonal population structure of C. hominis, genetic recombination has been shown to be a driving force for the emergence of virulent subtypes such as IbA10G2 and IaA28R4 Feng et al 2014).…”
Section: Multilocus Typing and Population Geneticsmentioning
confidence: 99%
“…The data have also facilitated the development of high-resolution molecular typing tools (4,9). Population genetic characterizations of C. parvum and C. hominis using these advanced molecular detection tools have started to improve our understanding of the genetic determinants for host specificity and virulence (10)(11)(12).…”
mentioning
confidence: 99%